2018
DOI: 10.1002/jcb.27639
|View full text |Cite
|
Sign up to set email alerts
|

miRNA profiling in the hippocampus of attention‐deficit/hyperactivity disorder rats

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is characterized by attention deficit, hyperactivity, impulsivity, and learning and memory impairment.Although the pathogenesis of learning and memory impairment is still unknown, some studies have suggested an association with hippocampus dysfunction. We aimed to explore the role of miRNAs in the learning and memory impairments observed in ADHD. Differentially expressed hippocampal micro-ribonucleic acids (miRNAs) in spontaneously hypertensive rats (SHRs) and Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…We found that 17 miRNAs whose expression was changed in mice hippocampus by BPA. Bioinformatics analysis was conducted to further study the potential roles of the target genes regulated by these deregulated miRNAs [ 47 ]. GO analysis suggested that target genes of these miRNAs were closely associated with regulation of central nervous system structure and function, including several cognitive processes, especially the learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 17 miRNAs whose expression was changed in mice hippocampus by BPA. Bioinformatics analysis was conducted to further study the potential roles of the target genes regulated by these deregulated miRNAs [ 47 ]. GO analysis suggested that target genes of these miRNAs were closely associated with regulation of central nervous system structure and function, including several cognitive processes, especially the learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-764-3p was down-regulated in the hippocampus of rats with dementia [ 70 ]. miR-741-3p was upregulated in attention-deficit/hyperactivity disorder rats [ 71 ]. miR-18a-5p was involved in axonogenesis in rat hippocampus by regulating its target genes [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-741-3p is a member of the fragile-X miRNA cluster [ 225 ] and was dramatically upregulated in rat models of nonalcoholic fatty liver disease [ 226 ] and attention-deficit/hyperactivity disorder [ 227 ]. A previous study showed protection of miR-741-3p against radiation-induced injury of bone mesenchymal stem cells [ 228 ].…”
Section: Modulation Of Microglia For Ribi Therapymentioning
confidence: 99%